2011
DOI: 10.5152/jaem.2011.062
|View full text |Cite
|
Sign up to set email alerts
|

CO Poisoning Without Obvious Source: A Case Report

Abstract: Carbon monoxide (CO) poisoning is responsible for a great number of unintentional deaths all over the world. The diagnosis is very difficult due to its various symptoms that mimic numerous illnesses. Misdiagnosis can lead to cell death and cognitive deficits which are irreversible. Therefore, knowing the situations in which CO poisoning occurs is of great importance in clinical suspicion and evaluation. The most common ones are listed by the Centers for disease control and prevention of the United States. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…We read with interest the article by Sayedjavady et al (1 ) entitled "CO poisoning without obvious source: a case report", where they reported four cases of carbon monoxide (CO) poisoning. The authors noted that all oftheir cases sustained CO poisoning following having a shower and drew attention to the fact that none ofthe bathrooms contained water heaters, which were installed in the kitchen or basement instead.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the article by Sayedjavady et al (1 ) entitled "CO poisoning without obvious source: a case report", where they reported four cases of carbon monoxide (CO) poisoning. The authors noted that all oftheir cases sustained CO poisoning following having a shower and drew attention to the fact that none ofthe bathrooms contained water heaters, which were installed in the kitchen or basement instead.…”
mentioning
confidence: 99%
“…As a result, CO would accumulate in the house. Chronic and subtle CO exposure is a well-known and well-documented condition leading to various clinical pictures, as described above (1 ). Poorly functioning heating systems may cause CO production, and, unless significant enough to result in severe poisoning, chronic mild exposure will result in non-speeifie complaints such as chronic nausea, fatigue, headache, etc.…”
mentioning
confidence: 99%